Pengaruh Pendapatan Asli Daerah Dan Dana Perimbangan Terhadap Belanja Modal Aset Tetap Pada Pemerintah Kabupaten/Kota Di Provinsi Lampung - Sintia Lestari; Muhammad Luthfi; Kusnadi Kusnadi (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2015)
Abstract,This study is aimed to test the effect of Local Government Revenue (PAD) and TransferFunds in allocating Capital Expenditure in districts/cities in Lampung Province. The analyticalmethod for determining statistical tests with SPSS (Statistical Package for the Social) 17.00 software,with 10 regency/city as sample for every year from 14 regency/city at Lampung Province. Thisresearch is done for 2007-2012. The data used is Budget Realization Statements of districts/cities inLampung by Dirjen Perimbangan Keuangan Pemerintah Daerah (www.djpk.depkeu.go.id). Based onthe results of this study concluded that either altogether or in partial test, Local Government Revenue(PAD) and Transfer Funds did not significantly influence to Capital Expenditure fixed assets.